P 16 Effects of pallidal deep brain stimulation on striatal medium spiny neurons in the animal model of the dystonic dtsz mutant hamster. (May 2022) - Franz, D.; Heerdegen, M.; Engel, N.; Lüttig, A.; Perl, S.; Plocksties, F.V.; Richter, A.; Köhling, R.
Abstract : Introduction: Electric stimulation of the deep brain nuclei, such as globus pallidus internus (GPi), indicated the most relevant therapeutic option for patients with severe dystonias. However, the mechanisms of the deep brain stimulation (DBS) of the GPi are far from understood. Dystonia, a hyperkinetic movement disorder, is thought to result from an imbalance in the direct and indirect pathway arises from disturbance in the striatum. In the dt sz mutant hamster, a model of inherited generalized, paroxysmal dystonia, it has been already shown that the number of parvalbumin-positive gabaergic interneurons declined, which leads to uncontrolled projections via the medium spiny neurons (MSN) (see also Paap, et al. (2020), DOI: 10.1016/j.nbd.2020.105163). We hypothesized that DBS via backfiring, or indirectly via thalamic and cortical coupling, modifies striatal network function. Materials & Methods: The dt sz mutant hamsters were bilaterally implanted with stimulation electrodes targeting the entopeduncular nucleus (EPN; equivalent of the human GPi). DBS (130 Hz, rectangular pulse of 50 µA and 60 µs) and sham-DBS was performed in vivo in unanaesthetized animals for three hours. Acute brain slices of stim- and sham-groups were immediately prepared after the DBS has been terminated. Additionally, acute brain slices were obtained from untreated dt sz mutant hamsters (native group) to assess the effects of electrode implantation. With whole-cell patch clamp recordings, we investigated the spontaneous cortico-striatal synaptic activity and the characteristics of the D1- (direct pathway) and D2- (indirect pathway) MSN, which are capable of being differentiated by adding the D2-agonist sumanirole. Additionally, molecular analysis was performed for studying the DBS effect on ion channel gene expression. Results: In view of spontaneous release activity from cortical projections, our study indicated a strong dampening effect on the frequency of spontaneous miniature excitatory postsynaptic currents (mEPSC) of the stim-group in contrast to sham-group. The specific cellular parameters of D1- and D2-MSN, which include resting membrane potential, input resistance, membrane capacity, rheobase, and firing properties of action potentials, did not differ between native-, sham-, and stim- group. Conclusions: To conclude, while short-term EPN-DBS obviously dampens spontaneous presynaptic glutamate release at cortico-striatal synapses, there is no alteration on MSN properties. Future studies will consider the effects of long-term stimulation on synaptic plasticity by a novel implantable stimulation system which enables DBS over weeks (see also Plocksties et al. (2021). DOI: 10.1088/1741-2552/ac23e1). This study is supported by the German Research Foundation (DFG) within the Collaborative Research Centre (SFB 1270/1 ELAINE 299150580)